O gênero tira em materiais didáticos - Pinto, Juliana Fermino [UNESP] (2015)
This dissertation presents a reflection about presence of genres in teaching mother tongue; subject based in the National Curriculum Parameters (PCNs) of Fundamental Education of Portuguese Language, published in 1998. According to these NCPs, the main objective of Portuguese language teaching is the development of discursive competence of the students, that is develop in students the ability to choose the appropriate genre to different communicative situations. Dolz and Schneuwly (2004) believe that the principle of school work must be the genre, because in addition to collaborate for the development of students' language, also can be used as a teacher's working tools in the classroom. In this research we aimed to analyze the proposed activities with the genre strip on two different collections of Textbook of Portuguese Language (LDLP) of Fundamental Education II, adopted in State public institutions in the state of São Paulo. We chose the genre strip because we believe that it is a genre with characteristics able to conduct the students for a critical formation and citizen. Furthermore, we believe that the multimodal aspects of this genre may also contribute to the process of textual comprehension because, in certain communicative situations and with certain objective, non-verbal aspects are as important as speech and writing. We cannot consider it as a easy to interpret genre by its massive presence in diverse social contexts and their association with verbal language images, after all, is rightly this set of language verbal and non-verbal that requests diversified strategies to read, understand and learn. For the development of this research, we analyzed a corpus of 14 gifts strips in selected LDLP. Supported by Dionísio (2005, 2008), Marcuschi (2010), Ramos (2009), Vergueiro (2007), Vergueiro and Ramos (2013), among others, we reflect on the educational proposals of this genre in LDLP...